Pengaruh Psychological Capital terhadap Work Engagement pada Barista di Kota Bekasi - Raisha Nur Azizah; Rositawati, Sita (Bandung Conference Series: Psychology Science, 2024)
Abstract. Effective and efficient results are displayed by employees who are able to encourage and submit all their abilities by being fully involved in their work (Bakker, 2011). Research by Bakker & Demerouti (2008) shows that work engagement can be predicted by psychological capital as a personal resource that will lead to higher performance, due to the ability to adapt to various challenges. The aim of this research is to empirically test the influence of psychological capital on work engagement in the business and service sectors. The subjects of this research consisted of 107 baristas who had certificates and worked in informal coffee shops in Bekasi City. The sample was selected using a convenience sampling technique. This research uses quantitative methods and a causality research design that applies multiple regression techniques. The measurement scale uses the Psychological Capital Questionnaire (PCQ) instrument developed by Luthans et al. (2007), as well as the Utrecht Work Engagement Scale (UWES) from Schaufeli & Bakker (2003). Research data proves that there is a significant influence of psychological capital on work engagement of 41.40% (R Square = 0.414). The psychological capital dimension that has the strongest influence on work engagement is self-resilience at 14.33%, while the self-efficiency dimension does not have a significant influence (2.74%). Abstrak. Hasil efektif dan efisien ditampilkan oleh karyawan yang mampu mendorong dan menyerahkan segala kemampuannya dengan terlibat (engaged) secara penuh terhadap pekerjaannya (Bakker, 2011). Penelitian Bakker & Demerouti (2008) menunjukan bahwa work engagement dapat diprediksi oleh psychological capital sebagai personal resource akan mengarah pada kinerja yang lebih tinggi, dikarenakan kemampuannya untuk menyesuaikan diri dengan berbagai tantangan. Tujuan penelitian ini yaitu untuk menguji secara empiris pengaruh psychological capital pada work engagement dalam sektor bisnis dan layanan. Subyek penelitian ini terdiri dari 107 barista yang memiliki sertifikat dan bekerja di coffee shop informal di Kota Bekasi. Sampel dipilih dengan cara teknik convenience sampling. Penelitian ini menggunakan metode kuantitatif serta dengan desain penelitian kausalitas yang menerapkan teknik regresi berganda. Skala pengukuran dengan cara instrumen Psychological Capital Questionnaire (PCQ) yang dikembangkan oleh Luthans et al. (2007), serta Utrecht Work Engagement Scale (UWES) dari Schaufeli & Bakker (2003). Data hasil penelitian membuktikan bahwa ada pengaruh signifikan psychological capital terhadap work engagement sebesar 41,40% (R Square = 0,414). Dimensi psychological capital yang memiliki pengaruh paling kuat pada work engagement adalah ketahanan diri (resilience) sebesar 14,33%, sementara dimensi self-efficacy tidak memiliki pengaruh yang signifikan (2.74%).